Centralized bidding mechanism of demand response based on blockchain. (August 2022) - Mao, Xiaobo; Xue, Mingfeng; Zhang, Tianhan; Tan, Weitao; Zhang, Zhi; Pan, Yongtao; Wu, Hansong; Lin, Zhenzhi
Abstract: In future power systems with the characteristics of high-elastic, demand response (DR) is considered to be an essential way for improving system stability and awakening demand-side resources. However, all the DR programs in China are implemented in a centralized model, which is easier for supervision, but hard to deal with the challenges of data credibility, privacy protection, transaction efficiency, and so on. Therefore, a novel blockchain-based framework for the DR program is proposed to deal with the problems. On this basis, the bidding transaction process based on the repeated verification mechanism is designed, and the effectiveness of blockchain in DR is analyzed. Then, the smart contract functions involved in DR bidding transactions and subsidy settlement are customized. The feasibility of the DR bidding mechanism is illustrated by the simulation results on the platform of Remix IDE.